Weaving "Equity, Belonging and Power/Authority" for Pasifika into the Law Schools and Universities in Aotearoa New Zealand - Tupou Vaitohi, Mele (Victoria University of Wellington Law Review, 2023)
The report (Fofola na ibe) of the "Improving Pasifika Legal Education Project" concluded that the law schools in New Zealand have not served Pasifika peoples well. The reasons for this are diverse, and the range of possible solutions are complex. For many Pasifika peoples, the law school is inherently foreign to their views and values. Armed with the findings and recommendations of the report, this article uses the Pasifika weaving conception to reflect on the ways that law schools in New Zealand can ensure, through discussion, dialogue and action, that they are a just, equitable and welcoming place for Pasifika law students.